2013
DOI: 10.1093/nar/gkt198
|View full text |Cite
|
Sign up to set email alerts
|

Structures of DNA duplexes containing O6-carboxymethylguanine, a lesion associated with gastrointestinal cancer, reveal a mechanism for inducing pyrimidine transition mutations

Abstract: N-nitrosation of glycine and its derivatives generates potent alkylating agents that can lead to the formation of O6-carboxymethylguanine (O6-CMG) in DNA. O6-CMG has been identified in DNA derived from human colon tissue, and its occurrence has been linked to diets high in red and processed meats. By analogy to O6-methylguanine, O6-CMG is expected to be highly mutagenic, inducing G to A mutations during DNA replication that can increase the risk of gastrointestinal and other cancers. Two crystal structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
6
20
1
Order By: Relevance
“…24,46,47 Despite the limited activity of Pol ι, it could be shown that the enzyme displayed a preference for incorporating dTMP over dCMP opposite O 6 -CMG, which corresponds as well with previous observations for the bypass of O 6 -alkylG adducts by Pol ι. 24,48 30,31 However, the latter is derived from a structure of the free duplex and does not account for the important influences of the enzyme. In contrast to Pol η and κ, Pol ι had no PLS activity, suggesting that its role, if any, in O 6 -CMG bypass may be for the insertion rather than extension step.…”
Section: Scheme 2 Synthesis Of ! 6 -Carboxymethylguaninephosphoramiditementioning
confidence: 99%
See 1 more Smart Citation
“…24,46,47 Despite the limited activity of Pol ι, it could be shown that the enzyme displayed a preference for incorporating dTMP over dCMP opposite O 6 -CMG, which corresponds as well with previous observations for the bypass of O 6 -alkylG adducts by Pol ι. 24,48 30,31 However, the latter is derived from a structure of the free duplex and does not account for the important influences of the enzyme. In contrast to Pol η and κ, Pol ι had no PLS activity, suggesting that its role, if any, in O 6 -CMG bypass may be for the insertion rather than extension step.…”
Section: Scheme 2 Synthesis Of ! 6 -Carboxymethylguaninephosphoramiditementioning
confidence: 99%
“…Furthermore, recent crystal structures of DNA containing O 6 -CMG suggest a chemical basis for the mispairing involving a Watson-Crick-type or high-wobble-type O 6 -CMG:T pair. 30,31 Nevertheless, to our knowledge, no data is available regarding O 6 -CMG as a substrate for TLS catalyzed by human DNA polymerases, therefore its miscoding properties are not known.…”
mentioning
confidence: 99%
“…[14] O 6 -Carboxy-methylguanine (O 6 -CMG,F igure 1a)i sa ni mportant O 6 G lesion because it shows ahigh tendency to cause miscoding in DNAr eplication. [15] Indeed its appearance in vivo is proportional to the consumption of red meat and may lead to colorectal cancer. [16] Precise detection of O 6 -CMG within the genome is important to unveil the mechanisms of its formation, to determine whether certain sites are resistant to repair, [11a] or to explore its potential as at umor biomarker.…”
mentioning
confidence: 99%
“…1) containing O 6 -CMG at residue positions that place the modified base opposite T or C in the palindromic Bform Dickerson-Drew sequence d(CGCGAATTCGCG) (Dickerson & Drew, 1981). This revealed that O 6 -CMG forms a Watson-Crick-type pair with T similar to the canonical A:T pair and forms a reversed-wobble pair with C (Zhang et al, 2013). These interaction geometries are those expected from the chemical structure of O 6 -CMG.…”
Section: Introductionmentioning
confidence: 76%
“…All of the global and local helical parameters, as well as the torsion angles and pseudo-rotation phase angles of the sugar rings, were calculated using 3DNA (Lu & Olson, 2003). Some of these are given in Supplementary Tables S1, S2 and (Zhang et al, 2013), which required the addition of Hoechst 33258 to facilitate their crystallization. In contrast, the present ODN d(CGC[O 6 -CMG]AATTTGCG) (O 6 -CMG4T) was easily crystallized: four crystal forms were obtained under different conditions, two of which were obtained in the absence of Hoechst 33258.…”
Section: Structure Determination and Refinementmentioning
confidence: 99%